INDONESIAN SCHOLARPLAN : CREATIVE SOLUTIONS TO INCREASE VEGETABLE CULTIVATION COMPETENCIES EARLY IN CLASS 3 AND 4 MADRASAH IBTIDAIYAH AL-IKHLAS DUSUN SIDOMULYO - Agustina, Sela; Pristiyono, Pristiyono; Safri, Hayanuddin (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Vegetables are a general term for plant foods that usually contain high water content, vegetables are very beneficial for health, development and growth, especially consumed for children, especially elementary school age who are still in the period of development and growth, the nutrients contained in vegetables are: Fiber is needed by our body for metabolic processes. In addition to fiber, vegetables also contain vitamins needed to prevent various diseases such as night blindness (lack of vitamin A), beriberi (lack of vitamin B), canker sores (lack of vitamin C), and others. For this reason, socialization of vegetable cultivation is carried out so that students of Madrasah Ibtidaiyah Al-Ikhlas know and understand the meaning of vegetables, types of vegetables, benefits and content contained in vegetables, the impact of not consuming vegetables, and how to grow vegetables properly and correctly. The method used in the PKM program at Madrasah Ibtidaiyah Al-Ikhlas in Sidomulyo Hamlet is to increase students' knowledge of the importance of consuming vegetables, carried out by the lecture method, namely by providing an explanation accompanied by material that has been prepared previously in the form of power points, the discussion method is question and answer between the presenters and students about the material that has been delivered, and the training method is the practice of how to grow vegetables from preparing planting media, selecting seeds, nursery, and planting. The results of the socialization activities were that students were very enthusiastic about participating in the socialization and listening and paying close attention when the service team delivered material to practice vegetable cultivation methods.